EVALUASI KEBIJAKAN KURIKULUM MERDEKA DENGAN MENGGUNAKAN MODEL WILLIAM DUNN - Daryati Dewi Nur Nadila (LPPM Universitas Muhammadiyah Bulukumba, 2023)
Abstract: The independent curriculum policy is a new policy program by the Ministry of Education and Culture that focuses on increasing the minimum in the form of literacy, numeracy, and character surveys. This curriculum was enacted to improve the existing system in the previous curriculum. In its implementation, often many educational institutions experience obstacles in carrying out the independent curriculum policy. Therefore, evaluation is needed to see weaknesses, strengths, and implementation in the field. The purpose of this study was to evaluate the implementation of the independent curriculum policy using the William Dunn model. This research uses qualitative research methods with a type of library research approach by exploring information through literature regarding the evaluation of independent curriculum policies using the William Dunn model. The criteria for policy recommendations are the same as policy evaluation criteria, including: effectiveness, efficiency, adequacy, equity, responsiveness, amf appropriateness. Keywords: evaluation, William Dunn policy, merdeka curriculum